LEGAL BASIS AND TACTICS OF THE APPLICATION OF KUBOTAN SPECIAL TOOL BY MILITARY OFFICERS OF THE NATIONAL GUARD OF UKRAINE DURING THE PERFORMANCE OF PUBLIC ORDER PROTECTION AND PUBLIC SECURITY TASKS - Batiuk, Oleh; Bielai, Serhii; Volkov, Ihor (Honor and Law, 2023)
The article describes the provisions of regulatory legal acts that define the principles of normative and legal, service and combat application of the Kubotan technique by the servicemen of the National Guard of Ukraine for performing the task of protecting public safety and order. The analysis of regulatory legal acts and subordinate regulatory documents governing the list of special means, is carried out that are used by military personnel of the National Guard in the performing of official tasks and the rules for the use of special means by servicemen of the National Guard in the performance of authorised tasks in general and for the protection of public safety and order in particular. The legal essence and formation of the Kubotan, the characteristics and parameters of the Kubotan, the purpose and types of the Kubotan, and the technique of using the Kubotan by the servicemen of the National Guard of Ukraine to perform the task of protecting public security and order are described. The author defines the prohibition of the use of special means of Kubotan against women with obvious signs of pregnancy, minors, persons with obvious signs of disability or old age, except in cases of armed or group attack, armed resistance to a serviceman of the National Guard of Ukraine, threatening his life and health and/or other persons, if it is impossible to repel such attack or resistance by other means. The servicemen of the National Guard of Ukraine are required to undergo special training and periodic testing of their ability to perform actions related to the use of the special means of the Kubotan and to provide first aid to victims. The use of Kubotan as a special means, the time of start and the intensity of its use shall be determined taking into account the current circumstances, the nature of the offence and the personality of the offender. When on duty as part of a group, the decision to use special means is taken by a duly appointed official responsible for ensuring public safety and order, or by the head of the operation or the commander of the relevant military unit (subdivision, group) of the National Guard of Ukraine. Servicemen acting individually shall make such decisions on the use of Kubotan independently. It is concluded that it is advisable to use the Kubotan technique by the National Guard of Ukraine to perform the task of protecting public safety and order if other forms of preliminary impact on offenders have not yielded the desired results.